Budget practices in the third sector: a study of civil society organizations in the state of Pernambuco (Research, Society and Development, 2023)
The article aimed to investigate the use of the budget in Civil Society Organizations (CSOs) in the state of Pernambuco. Therefore, the methodology involved a descriptive research, using a survey by electronic correspondence, with the use of a questionnaire applied to 25 entities associated with the Brazilian Association of NGOs (ABONG), which made up the effective universe of the research. As a return, 11 respondents were obtained (44%). The results revealed that all organizations prepare a budget, most annually and using a flexible budget, that all organizations disclose the budget, varying only in relation to the public to which it is disclosed. It was also observed that most believe that there is an improvement in the organization's management process with the use of budget techniques and that all agree that the use of the budget is very important in the organization's management. Thus, it is concluded that the budget presents itself as a tool present in the administration of these institutions, which can contribute to the achievement of the proposed goals and objectives, as well as to the fulfillment of the entities' mission.